2018
DOI: 10.1016/j.athoracsur.2018.04.074
|View full text |Cite
|
Sign up to set email alerts
|

Adding Radiotherapy to Adjuvant Chemotherapy Does Not Improve Survival of Patients With N2 Lung Cancer

Abstract: In a large database study, the addition of radiotherapy to adjuvant chemotherapy after resection of N2 NSCLC was not associated with improved survival. Until more definitive data are available, consideration should be given to treating patients with N2 disease detected at resection with adjuvant chemotherapy only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 29 publications
1
7
0
1
Order By: Relevance
“…A post hoc analysis of the Adjuvant Navelbine International Trialist Association (ANITA) trial supported the use of adjuvant chemoradiation [3], but meta-analyses and randomized trials have failed to demonstrate a benefit of adding radiation to adjuvant chemotherapy [4,5]. Our work using a propensity-matched cohort from the National Cancer Database did not demonstrate any benefit of adding radiation therapy in patients with clinical N0 disease found to have N2 disease at operation [6].…”
Section: Reply To the Editormentioning
confidence: 74%
“…A post hoc analysis of the Adjuvant Navelbine International Trialist Association (ANITA) trial supported the use of adjuvant chemoradiation [3], but meta-analyses and randomized trials have failed to demonstrate a benefit of adding radiation to adjuvant chemotherapy [4,5]. Our work using a propensity-matched cohort from the National Cancer Database did not demonstrate any benefit of adding radiation therapy in patients with clinical N0 disease found to have N2 disease at operation [6].…”
Section: Reply To the Editormentioning
confidence: 74%
“…A recent randomized Phase II trial by Sun et al found no survival benefit for adjuvant concurrent chemoradiotherapy compared with adjuvant platinum-based chemotherapy alone (20). This finding has been supported by previous retrospective studies as well that suggest that there are no overall survival benefits to addition of adjuvant radiotherapy versus adjuvant chemotherapy alone (10,13,21). The findings of Sun et al must be interpreted cautiously, however, as sequential radiotherapy administered after adjuvant chemotherapy, rather than concurrent chemoradiotherapy, is more frequently performed (8,22,23).…”
Section: Discussionmentioning
confidence: 89%
“…However, some clinical trials revealed that PORT could only improve the local control of stage IIIA/N2 NSCLC, but failed to bring DFS or OS benefit ( 7 - 8 ). The phase III RCT, NCT00880971, enrolled 364 completely resected stage IIIA/N2 NSCLC patients from 2009 to 2017 ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…PORT could improve the local control, 5-years survival rate, and OS time ( 5 - 6 ). Unfortunately, some other studies found that PORT failed to bring disease-free survival (DFS) or OS benefit ( 7 - 8 ). The randomized controlled trials (RCTs) showed that PORT could only increase local recurrence-free rate ( 9 - 10 ).…”
Section: Introductionmentioning
confidence: 99%